A Lacanian Reading of Hamlet: The Mourning Subject of Desire - Marín Calderón, Norman (2015)
This paper analyzes Shakespeare’s Hamlet as an interwoven drama between desire and death. Hamlet takes his desire as an enigma because he does not know what to do with it nor when to act accordingly. For Lacan, Hamlet is trapped in the alienated webs of the capitalized Other who, unconsciously, points him what and how to desire. At this crossroads, Hamlet appropriates his (M)other Gertrude and his beloved Ophelia in order to place them as the objects of his desire, that is, as his signified phallus. Therefore, for Lacan, Hamlet is the tragedy of desire.